Use of a multi‐metric macroalgal index to document severe eutrophication in a New Zealand estuary - Leigh M. Stevens; Barrie M. Forrest; Bruce D. Dudley; David R. Plew; John R. Zeldis; Ude Shankar; Arman Haddadchi; Keryn L. Roberts (New Zealand Journal of Marine and Freshwater Research, 2022)
Environmental indicators that reliably describe estuary trophic response to nutrient loading are required for the effective management of New Zealand estuaries. A common estuary eutrophication response is frequent, extensive and persistent opportunistic macroalgae blooms. This study explores the utility of the Opportunistic Macroalgal Blooming Tool (OMBT) in the New River Estuary (∼4600 ha), a shallow intertidal‐dominated system within a pastoral farming catchment in Southland, New Zealand. Total nitrogen (TN) loads increased from 3206 T y −1 in 2000 to 5143 T y −1 in 2020. Concomitantly, areas of opportunistic macroalgae, measured using the OMBT, expanded across the available intertidal habitat (AIH) from 34.9 ha or 1.4% of the AIH to 1383 ha or 47.6% of the AIH, and the average wet weight biomass increased from 19.3 g m −2 to a peak of 1326 g m −2 in 2019. We hypothesise that opportunistic macroalgae expanded rapidly in direct response to temporal increases in TN load, with increases disproportionately contributed by expansion and intensification of dairy farming in the catchment. This study confirmed that the OMBT predictably responded to changes in TN concentration and may therefore be useful in defining estuary‐specific TN concentration thresholds to inform likely load reductions required to achieve improved environmental outcomes.